CBIO-24. NF2 LOSS-OF-FUNCTION COOPERATES WITH HYPOXIA TO DRIVE RADIATION RESISTANCE IN GRADE 2 MENINGIOMAS. (12th November 2021) - Patel, Bhuvic; Mahlokozera, Tatenda; Lu, Hsiang-Chih; Yang, Alicia; Mao, Diane; Sinha, Namita; Dahiya, Sonika; Petti, Allegra; Patel, Akash; Kim, Albert
Abstract: World health organization grade 2 meningiomas (G2M) are associated with an aggressive natural history characterized by frequent recurrence, resistance to radiation therapy (RT), and poor survival. We and others have shown that intratumoral necrosis is an independent predictor of disease progression in G2Ms treated with RT, suggesting that necrosis is a histopathological biomarker of radiation resistance. However, the mechanisms of radiation resistance in G2M remain unclear and treatment of radioresistant G2M is challenging. We performed genetic sequencing and histopathological analysis of 121 G2Ms and found that NF2 mutations are associated with intratumoral necrosis. To further investigate the relationship between NF2 loss-of-function, necrosis, and radiation resistance, we developed an in vitro model system using the IOMM-Lee meningioma cell line. In clonogenic survival assays, we found that NF2 knockdown under normoxia had little to no effect on radiation resistance compared to control. However, in the setting of hypoxia, NF2 knockdown significantly increased radiation resistance by maintaining cellular proliferation without impacting cell death. To understand the molecular basis of NF2 loss-of-function on radiation resistance, we performed bulk RNA sequencing of cells in our in vitro hypoxia/RT model and 10 patient G2Ms (5 necrotic and 5 non-necrotic tumors). GO and KEGG pathway analysis of the in vitro dataset revealed that NF2 deficiency triggers upregulation of pathways involved in DNA damage repair and cellular proliferation. Integration of differentially expressed genes between the in vitro NF2 loss-of-function model and necrotic patient tumors identified shared upregulation of S100A4, which promotes cell cycle progression, and downregulation of WNK2, a cell proliferation inhibitor. Together, these results suggest NF2 loss-of-function in the setting of hypoxia confers radiation resistance through a transcriptional program that promotes proliferation and DNA repair.